2012
DOI: 10.1152/ajpheart.00060.2012
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic administration of IL-11 exhibits the postconditioning effects against ischemia-reperfusion injury via STAT3 in the heart

Abstract: Activation of cardiac STAT3 by IL-6 cytokine family contributes to cardioprotection. Previously, we demonstrated that IL-11, an IL-6 cytokine family, has the therapeutic potential to prevent adverse cardiac remodeling after myocardial infarction; however, it remains to be elucidated whether IL-11 exhibits postconditioning effects. To address the possibility that IL-11 treatment improves clinical outcome of recanalization therapy against acute myocardial infarction, we examined its postconditioning effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 29 publications
2
69
1
Order By: Relevance
“…STAT3 iCKO mice were generated as previously described with minor modifications (20). Briefly, STAT3 flox mice were bred with transgenic mice expressing TM-inducible Cre recombinase fused to mutated estrogen receptor (MerCreMer) under the control of the cardiomyocyte-specific ␣-MHC promoter to produce ␣-MHCMerCreMer/STAT3 flox/flox mutant mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…STAT3 iCKO mice were generated as previously described with minor modifications (20). Briefly, STAT3 flox mice were bred with transgenic mice expressing TM-inducible Cre recombinase fused to mutated estrogen receptor (MerCreMer) under the control of the cardiomyocyte-specific ␣-MHC promoter to produce ␣-MHCMerCreMer/STAT3 flox/flox mutant mice.…”
Section: Methodsmentioning
confidence: 99%
“…STAT3 plays protective roles against acute myocardial injury, such as ischemia and ischemia-reperfusion (19,20). In contrast, a recent study (10) has shown that continuous activation of STAT3 mediated by glycoprotein (gp)130 promotes adverse outcome in subacute myocardial infarction (MI) in constitutively active gp130 mutant mice.…”
Section: New and Noteworthymentioning
confidence: 99%
“…1, B and C, and Table 1). At 1 h of treatment, eight of the top 10 genes disproportionately up-regulated by mOSM-LIFR were Socs3 (26), Cxcl1 (27), Zfp36 (28), Mt2 (29), Sbno2 (30), Bcl3 (31), Junb (32), and Fos (33) (Fig. 1B).…”
Section: Identification Of Downstream Gene Signatures By Microarray-mentioning
confidence: 99%
“…Notably, administration of IL-11 after inducing myocardial infarction, which was generated by coronary ligation, ameliorated the post-infarct cardiac dysfunction. The post-ischemic treatment with IL-11 prevented cardiac fibrosis, reduced the frequency of cell death, and promoted angiogenesis (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Optimization of the dose and timing of IL-11 administration was not considered in this study but is an important topic as it may influence the outcome. What formed the basis of the present dosing strategy was the results of our previous IL-11 studies (3)(4)(5). In a study using a mouse myocardial IR injury model, the animals pretreated with 8 μg/kg of IL-11 had a significantly reduced infarct size (4).…”
Section: Discussionmentioning
confidence: 99%